Transcriptional Signatures in Liver Reveal Metabolic Adaptations to Seasons in Migratory Blackheaded Buntings - Singh, Devraj; Swarup, Vivek; Le, Hiep; Kumar, Vinod (Frontiers in Physiology, 2018)
The molecular underpinnings of metabolic adaptation to seasons are poorly understood in long- distance migrants. We measured changes in the physiology and performed de-novo sequencing of RNA extracted from the liver samples collected at 4 h intervals over a 24 h period from a long-distance avian migrant, the blackheaded bunting (Emberiza melanocephala) during two states: the photostimulated vernal migratory (M) state and the photorefractory non-migratory (nM) state. The M state was differentiated from the nM state based on body fattening and weight gain, as well as on Zugunruhe, i.e. nocturnal migratory restlessness in caged birds. We found that baseline blood glucose and triglyceride levels were significantly higher in M than the nM state; conversely, the surface body temperature was higher in nM state than the M state. In a total of 6 liver samples that were sequenced from each state, 11,246 genes were annotated including 4448 genes that were cyclic over 24 h. We found 569 differentially expressed genes (DEGs) between the M and the nM state, and the M state showed 131 up- and 438 down-regulated genes. These DEGs formed core gene hubs associated with specific biological processes in both the states. Further, weighted gene co-expression network analysis revealed two discrete modules of co-expressed genes, with a significant difference in the expression pattern of metabolism-associated genes between the M and nM states. These results demonstrate for the first time so widely transcriptome-wide changes in the liver between two distinct physiological states, and give molecular insights into seasonal metabolic adaptations in latitudinal migrants.